2018
DOI: 10.1002/lno.11055
|View full text |Cite
|
Sign up to set email alerts
|

On contributions by wind‐induced mixing and eddy pumping to interannual chlorophyll variability during different ENSO phases in the northern South China Sea

Abstract: The chlorophyll in the northern South China Sea (NSCS) shows strong interannual variability between different phases of the El Niño‐Southern Oscillation (ENSO), primarily due to the influence from Kuroshio intrusion. Chlorophyll observations also reveal that significant year‐to‐year variation remains in the same ENSO phase, but its controlling mechanism is unknown. In this study, we examined driving mechanisms for such regional ecosystem variability on a year‐to‐year timescale. Using observational data and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, the distribution of PHY in 2011 reflected that the range and the value of high PHY areas in the northern gulf was greater than in 2011 and 2015, indicating that the lower sea temperature in the La Niña year was more conducive to PHY growth in the Beibu Gulf [61]. In the La Niña phase, the wind strengthened, resulting in an increase in CV and seawater mixing, so the concentration of PHY increased [62,63]. From the results of the model simulated outputs (Figures 9-11), we found that the La Niña year of 2011 had lower TEM in general, especially in the northern gulf, and the area of high PHY was larger than that of 2013 and 2015 in the northeastern gulf, but that it moved to south.…”
Section: The Climate Effectmentioning
confidence: 96%
“…Therefore, the distribution of PHY in 2011 reflected that the range and the value of high PHY areas in the northern gulf was greater than in 2011 and 2015, indicating that the lower sea temperature in the La Niña year was more conducive to PHY growth in the Beibu Gulf [61]. In the La Niña phase, the wind strengthened, resulting in an increase in CV and seawater mixing, so the concentration of PHY increased [62,63]. From the results of the model simulated outputs (Figures 9-11), we found that the La Niña year of 2011 had lower TEM in general, especially in the northern gulf, and the area of high PHY was larger than that of 2013 and 2015 in the northeastern gulf, but that it moved to south.…”
Section: The Climate Effectmentioning
confidence: 96%
“…The impact of a single typhoon on the ocean is quite different from the accumulated changes, and large responses are mainly identified in coastal regions (Figures 8b and 8e). Coastal regions are characterized by a weak stratification and small vertical difference (Xiu et al, 2018); thus, the typhoon-driven mixing is expected to induce small changes. However, the thermocline and nutricline near the coast are shallow (Wang et al, 2020), and the water column can be easily mixed by typhoons such that even a weak and fast-moving typhoon can induce a prominent change at the ocean surface (Zhao et al, 2017).…”
Section: 1029/2020jc016243mentioning
confidence: 99%
“…The LST varies as the bifurcation latitude of the North Equatorial Current shifts, which is strongly correlated with the ENSO (Nan et al., 2015; Yaremchuk & Qu, 2004). On the other hand, a shift in the scope of the intertropical convergence zone could directly impact the monsoon intensity and subsequent biological responses in the SCS (Tseng et al., 2009; C. Wang et al., 2006; Xiu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a shift in the scope of the intertropical convergence zone could directly impact the monsoon intensity and subsequent biological responses in the SCS (Tseng et al, 2009;C. Wang et al, 2006;Xiu et al, 2019).…”
mentioning
confidence: 99%